Dynamis - Chiurazzi, Gaetano. author. (orcid)0000-0003-3332-6931 Link aut Link
XIV, 179 p. 2 illus., 1 illus. in color.
Keywords: This book offers a new and original hypothesis on the origin of modal ontology, whose roots can be traced back to the mathematical debate about incommensurable magnitudes, which forms the implicit background for Plato’s later dialogues and culminates in the definition of being as dynamis in the Sophist. Incommensurable magnitudes – also called dynameis by Theaetetus – are presented as the solution to the problem of non-being and serve as the cornerstone for a philosophy of difference and becoming. This shift also marks the passage to another form of rationality – one not of the measure, but of the mediation. The book argues that the ontology and the rationality which arise out of the discovery of incommensurable constitutes a thread that runs through the entire history of philosophy, one that leads to Kantian transcendentalism and to the philosophies derived from it, such as Hegelianism and philosophical hermeneutics. Readers discover an insightful exchange with some of the most important issues in philosophy, newly reconsidered from the point of view of an ontology of the incommensurable. These issues include the infinite, the continuum, existence, and difference. This text appeals to students and researchers in the fields of ancient philosophy, German idealism, philosophical hermeneutics and the history of mathematics.